Processing and characterisation of standard and doped alite-belite-ye'elimite ecocement pastes and mortars - Zea-Garcia, Jesus D.; Gómez-de-la-Torre, María de los Ángeles; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel (My University, 2020)
Here, we report the processing optimisation of two laboratory-prepared alite-belite-ye'elimite ecocements (standard and doped) that release to the atmosphere ~13% less CO2 than Portland Cement during fabrication. The processing was optimised through rheological measurements, where homogeneous pastes and mortars were finally prepared through the study and optimisation of both the superplasticiser content and the water-to-cement ratio. Both parameters were correlated with the phase assembly of selected pastes and compressive strength of the corresponding mortars. After optimisation, mortars with high compressive strengths (~72 and ~77 MPa for the standard mortar, and ~41 and ~75 MPa for the doped one, at 7 and 28 days, respectively) were prepared. Furthermore, the important increase in compressive strength from 7 to 28 days of the optimised mortar prepared from the doped ecocement is due to its composition (the higher content of belite jointly with the reaction of its active polymorph (α'H-belite)).
Supplementary data to this article can be found online at https://doi.org/10.1016/j.cemconres.2019.105911.Cement and Concrete Research 127 (2020) 105911
Keywords: Cementos; Alite-belite-ye'elimite ecocements; Processing; Rheology; X-ray diffraction; Compressive strength